Effective Bandwidth for Deterministic Networks - Bachrata, Katarina (Communications - Scientific Letters of the University of Zilina, 2003)
In present paper are given exact definitions of the studied notions. Some elementary properties of an effective bandwidth are deduced. Some terms and results are illustrated with examples for finite as well as for infinite packet flows in the internet network.
Keywords: no keywords